Strong metal-metal coupling in mixed-valent intermediates [Cl(L)Ru(mu-tppz)Ru(L)Cl](+), L = beta-diketonato ligands, tppz=2,3,5,6-tetrakis(2-pyridyl)pyrazine - Kundu, Tanaya; Schweinfurth, David; Sarkar, Biprajit; Mondal, Tapan Kumar; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Dalton Transactions, 2012)
Five diruthenium(II) complexes [Cl(L)Ru(mu-tppz)Ru(L)Cl](1-5) containing differently substituted beta-diketonato derivatives (1: L = 2,4-pentanedionato; 2: L = 3,5-heptanedionato; 3: L = 2,2,6,6-tetramethyl-3,5-heptanedionato; 4: L = 3-methyl-2,4-pentanedionato; 5: L = 3-ethyl-2,4-pentanedionato) as ancillary ligands (L) were synthesized and studied by spectroelectrochemistry (UV-Vis-NIR, electron paramagnetic resonance (EPR)). X-ray structural characterisation revealed anti (1, 2, 5) or syn (3) configuration as well as non-planarity of the bis-tridentate tppz bridge and strong d pi(Ru-II) -> pi*(pyrazine, tppz) back-bonding. The widely separated one-electron oxidation steps, (RuRuII)-Ru-II/(RuRuIII)-Ru-II and (RuRuIII)-Ru-II/(RuRuIII)-Ru-III, result in large comproportionation constants (K-c) of >= 10(10) for the mixed-valent intermediates. The syn-configurated 3(n) exhibits a particularly high K-c of 10(12) for n = 1+, accompanied by density functional theory (DFT)-calculated minimum Ru-N bond lengths for this (RuRuIII)-Ru-II intermediate. The electrogenerated mixed-valent states 1(+)-5(+) exhibit anisotropic EPR spectra at 110 K with average values < g > of 2.304-2.234 and g anisotropies Delta g = g(1)-g(3) of 0.82-0.99. Metal-to-metal charge transfer (MMCT) absorptions occur for 1(+)-5(+) in the NIR region at 1660 nm-1750 nm (epsilon approximate to 2700 dm(3) mol(-1) cm(-1), Delta nu(1/2) approximate to 1800 cm(-1)). DFT calculations of 1(+) and 3(+) yield comparable Mulliken spin densities of about 0.60 for the metal ions, corresponding to valence-delocalised situations (Ru-2.5)(2). Rather large spin densities of about -0.4 were calculated for the tppz bridges in 1(+) and 3(+). The calculated electronic interaction values (V-AB) for 1(+)-5(+) are about 3000 cm(-1), comparable to that for the Creutz-Taube ion at 3185 cm(-1). The DFT calculations predict that the (RuRuIII)-Ru-III forms in 12(+)-52(+) prefer a triplet (S = 1) ground state with Delta E (S = 0 - S = 1) similar to 5000 cm(-1). One-electron reduction takes place at the tppz bridge which results in species [Cl(L)Ru-II(mu-tppz(.-)) Ru-II(L)Cl](-) (1(.-)-3(.-), 5(.-)) which exhibit free radical-type EPR signals and NIR transitions typical of the tppz radical anion. The system 4(n) is distinguished by lability of the Ru-Cl bonds.